EFEKTIVITAS BUAH PISANG AMBON TERHADAP TEKANAN DARAH IBU HAMIL HIPERTENSI DI KLINIK PRATAMA SARINAH - Nurul Hidayah Darmansyah (Jurnal Kebidanan, 2021)
Hypertension in pregnancy can be bad for the mother and the fetus. Hypertension in pregnancy is a major cause of maternal death during childbirth,and has a serious effect during childbirth, the cause of hypertension is not yet known with certainty. One of the non-pharmacological ways to reduce hypertension in pregnant women is to consume Ambon banana. The purpose of this study was to determine the effectiveness of Ambon bananas on blood pressure of pregnant women with hypertensionThis research method is a quasi-experimental design with One Group Pre-test-Post test. The total population in this study were 31 pregnant women, the sampling technique used consecutive sampling with a sample of 15 pregnant women. This research was conducted at the SarinahPratama Clinic, Pekanbaru from October 2020 to June 2021. The data analysis used was univariate and bivariate using Paired Sample T-Test. The bivariate results showed a P value of 0.000 and a value of 0.05, meaning that there was an effectiveness of Ambon banana to reduce hypertension in pregnant womenIt is hoped that the research site can provide information about the effectiveness of Ambon bananas in reducing blood pressure as a non-pharmacological drug.